Unfired Bricks Green Material with Microorganism Biocementation - Andi Marini Indriani; Gunaedy Utomo; Maslina; Yuninda Az’Zahrah; Zaerima Zahira Ochtharima (Jurnal Penelitian Pendidikan IPA, 2024)
The disposal of industrial sludge from Water Treatment Plants (WTP) poses environmental risks, particularly groundwater pollution. One solution is reusing this sludge in brick production, as clay use is unsustainable and may lead to shortages. This research investigates innovations in brick making, specifically using WTP sludge and the Microbially Induced Calcite Precipitation (MICP) technique with Bacillus huizhouensis to enhance brick strength. The MICP method produces calcium carbonate (CaCO₃) naturally, reinforcing bricks without harmful burning. After 50 days, compressive tests showed that bio-bricks with 15% WTP sludge and 25% bacteria achieved the highest strength of 3.79 MPa, compared to 1.49 MPa for mud bricks with only sludge. However, bio-bricks with 6% bacteria and 15% sludge reached only 1.74 MPa, with all values below the SNI 15-2094-2000 standard of 5 MPa.